2014
DOI: 10.1016/j.neuron.2014.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Glial Dysfunction Causes Age-Related Memory Impairment in Drosophila

Abstract: Several aging phenotypes, including age-related memory impairment (AMI), are thought to be caused by cumulative oxidative damage. In Drosophila, age-related impairments in 1 hr memory can be suppressed by reducing activity of protein kinase A (PKA). However, the mechanism for this effect has been unclear. Here we show that decreasing PKA suppresses AMI by reducing activity of pyruvate carboxylase (PC), a glial metabolic enzyme whose amounts increase upon aging. Increased PC activity causes AMI through a mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 54 publications
2
61
0
Order By: Relevance
“…Our analyses indicate that there are 49 genes with astrocyte-enriched expression encoding membrane transporters or ion channels, including Irk channels, the GABA transporter, an SLC5A transporter (CG9657) and GABA Transaminase ( GABAT ), a mitochondrial protein known to be expressed in glial cells and important for sleep regulation (Chen et al, 2015). Enriched or high-level expression was observed for other known fly glial genes in our analysis (Table S5): these encode Glutamine synthase 2, Glutamate oxaloacetate transaminase isoforms ( Got 1 and Got2 ), Dopamine acetyltransferase and Pyruvate decarboxylase (recently implicated in age-dependent memory impairment, Yamazaki et al, 2014). The glutamate transporter ( eaat1 ) gene is expressed in fly astrocytes (~800 reads) but was not enriched relative to total RNA in our analysis (~1300 reads).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Our analyses indicate that there are 49 genes with astrocyte-enriched expression encoding membrane transporters or ion channels, including Irk channels, the GABA transporter, an SLC5A transporter (CG9657) and GABA Transaminase ( GABAT ), a mitochondrial protein known to be expressed in glial cells and important for sleep regulation (Chen et al, 2015). Enriched or high-level expression was observed for other known fly glial genes in our analysis (Table S5): these encode Glutamine synthase 2, Glutamate oxaloacetate transaminase isoforms ( Got 1 and Got2 ), Dopamine acetyltransferase and Pyruvate decarboxylase (recently implicated in age-dependent memory impairment, Yamazaki et al, 2014). The glutamate transporter ( eaat1 ) gene is expressed in fly astrocytes (~800 reads) but was not enriched relative to total RNA in our analysis (~1300 reads).…”
Section: Resultsmentioning
confidence: 75%
“…Drosophila glia-neuron interactions are known to be important for development of the fly nervous system as well as normal and pathological neuronal degeneration that occurs in the adult brain (Doherty et al, 2009; Miller et al, 2012; Petersen et al, 2012; Hakim et al, 2014; Tasdemir-Yilmaz and Freeman, 2014), but only recently has it been documented that such interactions are important for adult behavior. Recent studies, for example, show that glia-neuron signaling in the Drosophila brain is an important component of circuit interactions that control neuronal excitability (Melom and Littleton, 2013; Rusan et al, 2014), circadian behavior (Ng et al, 2011; Jackson et al, 2015), sleep (Seugnet et al, 2011; Chen et al, 2015), olfaction (Liu et al, 2014), vision (Borycz et al, 2012; Rahman et al, 2012; Xu et al, 2015) and memory formation (Yamazaki et al, 2014; Matsuno et al, 2015). Given these findings, it is of interest to define glial factors, including secreted proteins, which mediate communication with neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Since the neuronal circuits of the mushroom bodies and central complex are known to regulate behaviors that are affected by aging, such as learning and memory, locomotor activity and walking (Martin et al, 1998, 1999; Grotewiel et al, 2005; Yamazaki et al, 2014; Ismail et al, 2015), we used antibody markers to study effects of dormancy and aging on these brain centers.…”
Section: Resultsmentioning
confidence: 99%
“…Only more subtle signs of aging have been revealed in the fly: central neurons do display some ultrastructural changes (Martín-Peña et al, 2006) and certain structural and molecular features were shown to be affected in axon terminations of motor neurons (Beramendi et al, 2007; Wagner et al, 2015). On the other hand, many behaviors, including learning and memory, are known to deteriorate over the lifespan (Grotewiel et al, 2005; Tonoki and Davis, 2012; Yamazaki et al, 2014) suggesting that aging induces deleterious effects on neurons and neuronal circuits in the Drosophila brain. One aim of this study is to reveal such aging-induced changes in brain neurons and try to relate them to behavioral senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, binding of D-serine to GluD2 leads to the acquisition of motor learning in mice [62]. Recently, it has been reported that the age-dependent increase in pyruvate carboxylase activity in glial cells causes a decrease in the level of D-serine, leading to age-related memory impairment in flies [63]. Pyruvate carboxylase generates oxaloacetic acid, which can be converted to aspartic acid.…”
Section: D-serinementioning
confidence: 99%